Depletion of RT6.1+ T lymphocytes alone is insufficient to induce diabetes in diabetes-resistant BB/Wor rats. - Like, A. A. (1990)
Diabetes-prone (DP) BB/Wor rats are lymphopenic, lack RT6.1+ T cells, and spontaneously develop diabetes mellitus. Diabetes-resistant (DR) rats are not lymphopenic, have normal numbers of RT6.1+ T cells, and rarely become diabetic. It has been reported that RT6.1+ T-cell depletion induced insulitis and diabetes in DR rats. To study the effector cells responsible for diabetes in DR rats after RT6+ T cell depletion, we treated a large number of intact and 21-day thymectomized DR rats with anti-RT6.1 monoclonal antibody, anticipating a high frequency of insulitis and diabetes. Our treatment protocol depleted RT6+ T cells but failed to induce insulitis and diabetes with the expected frequency in either intact or thymectomized DR animals. After Con-A stimulation however, RT6-depleted DR spleen cells readily transferred diabetes to DP recipients. These results suggested that while RT6+ T-cell depletion alone was permissive for the induction of diabetes in BB/Wor DR rats, a second stimulus was required to activate the DR effector cells responsible for insulitis and diabetes. In view of the occasional presence of pancreatitis and peritonitis in the diabetic RT6.1+ T-cell-depleted DR rats, additional experiments were performed in which RT6-depleted DR rats were also given intraperitoneal injections of sterile fecal suspensions to deliberately induce peritoneal inflammation. Insulitis and diabetes were significantly increased in these rats, lending credence to the requirement of a second (environmental) stimulus for the induction of diabetes in RT6-depleted BB/Wor DR rats.